Indomaret Promotion Systems in Pontianak City: Fiqh Muamalah Perspective - Primayudia, Doddy; Fitri, Amatul; Widiarni, Anis; Sari, Rani Puspita; Tanassy, Rika Putri (Tujjar International Journal of Islamic Economics Development, 2023)
One form of Muamalah that is most often done by humans in general is buying and selling. In buying and selling activities, the term Promotiontion is often encountered, one form of Promotiontion in buying and selling practices is price discounts or discounts. The purpose of this study is to find out the practice of buying and selling in the Promotion system at Indomaret and to find out how the employee regulations in the practice of buying and selling. This type of research belongs to field research, where data is obtained from primary data in the form of interviews and observations, while secondary data is obtained from literature and data documentation. As for the results of this study, namely in the practice of buying and selling in the Promotion system, buyers are required to fulfill the requirements for purchasing goods with a predetermined minimum total expenditure. Indomaret itself also has a period once a week in conducting Promotiontions. Regulations against employees are allowed to buy the product being Promotionted, even though there is no written regulation for the employee himself, but if he takes other people's rights in purchasing the product being Promotionted, he will get a verbal or written warning sanction if known by Indomaret. The legal basis for buying and selling at Indomaret must be the willingness of both parties in the transaction. Whereas in the perspective of fiqh Muamalah, the Promotion system in buying and selling practices at Indomaret, to be precise, on Jalan Jenderal Urip Pontianak, West Kalimantan City, is permissible as long as no party feels disadvantaged and in accordance with Islamic law.